The implementation of guidelines and standards for waterfront design and development at Lumut, Perak, Malaysia / Zarina Mohamed Nordin and Rafizah Mohamed Nordin - Mohamed Nordin, Zarina; Mohamed Nordin, Rafizah (2012)
Waterfront development in Malaysia hasbecome an issue that is of wide concern anddiscussed extensivelyfollowing numerous new waterfronts developments for various functions. The developments were based on the land use zoning and the waterfront location whether facing theriver, wetlands, lake or the coast. These two factors create different impacts to the existing environment. Through literature study, the main consideration and objective of the guidelines was determined. Other indicators such as the effects of waterfront development to the local environment, ecosystem and the responsibilities to rehabilitate, as well as preservation of the existing waterfront were highlighted as part of the main concern towards supporting the sustainable built environment. The local authorities at each stage have set up the guidelines and standards for waterfront development. To limit the scope of study, the Lumut Local Structure Plan for 1998 - 2010 provided by the Manjung Town Hall was reviewed. In order to come up with the list of recommendations as an addition to the existing standards, an observation was carried out at the Lumut Waterfront in Perak, Malaysia to analyze the implementation of the guidelines and standards on the its design and development. The findings of this study maybe adapted in the guidelines used by the other states in Malaysia. The significance of this research is to foster better understanding and awareness by both Local Authoritiesand the public in preserving waterfronts towards rehabilitating the natural ecosystem by putting the accent of sustainable design at the proposal stage.